Locating the Main Central Thrust in central Nepal using lithologic, microstructural and metamorphic criteria - Paudel, L. P.; Arita, K. (Journal of Nepal Geological Society, 2002)
Although the Main Central Thrust (MCT) is believed to be an intracrustal thrust extending throughout the length of the Himalaya, its nature and location is very much obscured and debated for many years. In the present work, field observations, microstructural analysis and metamorphic data there combined in a study along the Seti River and Modi Khola valleys in the Pokhara area of central Nepal to figure out recognizable criteria for objectively locating the MCT. The study demonstrates that the MCT is a sharp and discordant tectono-metamorphic boundary separating the Lesser and Higher Himalayas in the Pokhara area. The MCT is marked by changes in 1) lithology, 2) style of microfolding, 3) deformation of quartz and feldspars. 4) garnet texture, compositions and zoning patterns, and 5) muscovite and plagioclase compositions. We believe that some or all of the above changes should be observed across the MCT in other pans of the Himalaya and provide important criteria to locate the MCT.